Silence and Democracy : Athenian Politics in Thucydides' History - Zumbrunnen, John (Book collections on Project MUSE., 2008)
The role of elites vis--̉vis the mass public in the construction and successful functioning of democracy has long been of central interest to political theorists. In Silence and Democracy, John Zumbrunnen explores this theme in Thucydides' famous history of the Peloponnesian War as a way of focusing our thoughts about this relationship in our own modern democracy. In Periclean Athens, according to Thucydides, "what was in name a democracy became in actuality rule by the first man." This political transformation of Athenian political life raises the question of how to interpret the silence of the demos. Zumbrunnen distinguishes the "silence of contending voices" from the "collective silence of the demos," and finds the latter the more difficult and intriguing problem. It is in the complex interplay of silence, speech, and action that Zumbrunnen teases out the meaning of democracy for Thucydides in both its domestic and international dimensions and shows how we may benefit from the Thucydidean text in thinking about the ways in which the silence of ordinary citizens can enable the domineering machinations of political elites in America and elsewhere today